2021
DOI: 10.1111/gbb.12762
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment polygenic score predicts inhibitory control and academic skills in early and middle childhood

Abstract: Inhibitory control skills are important for academic outcomes across childhood, but it is unknown whether inhibitory control is implicated in the association between genetic variation and academic performance. This study examined the relationship between a GWAS-based (EduYears) polygenic score indexing educational attainment (EA PGS) and inhibitory control in early (M age = 3.80 years) and middle childhood (M age = 9.18 years), and whether inhibitory control in early childhood mediated the relation between EA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
(261 reference statements)
0
4
0
Order By: Relevance
“…Similarly, the educational attainment PGS was negatively associated with individual hyperactivity items. Previous evidence suggests higher educational attainment PGS predict lower ADHD symptoms and better inhibitory control . Indeed, our networks showed the educational attainment PGS was negatively associated with cheating, having poor attention, and being easily distracted and impulsive and positively associated with internalizing and peer problems, such as being solitary, having many worries, not being liked, and not volunteering to help others.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, the educational attainment PGS was negatively associated with individual hyperactivity items. Previous evidence suggests higher educational attainment PGS predict lower ADHD symptoms and better inhibitory control . Indeed, our networks showed the educational attainment PGS was negatively associated with cheating, having poor attention, and being easily distracted and impulsive and positively associated with internalizing and peer problems, such as being solitary, having many worries, not being liked, and not volunteering to help others.…”
Section: Discussionsupporting
confidence: 51%
“…PGS-EA has been significantly associated with vocabulary, executive function (inhibitory control, working memory), and episodic memory in children and adolescents (Domingue et al, 2015;Judd et al, 2020;Loughnan et al, 2021;Rea-Sandin et al, 2021).…”
Section: Pgs-ea Socioeconomic Factors and Neurocognitive Skillsmentioning
confidence: 99%
“…Although multiple studies have demonstrated associations between PGS‐EA and general cognitive ability (Plomin & von Stumm, 2018), a smaller body of work has shown associations between PGS‐EA and specific neurocognitive skills that underlie general cognitive ability. PGS‐EA has been significantly associated with vocabulary, executive function (inhibitory control, working memory), and episodic memory in children and adolescents (Domingue et al, 2015; Judd et al, 2020; Loughnan et al, 2021; Rea‐Sandin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiple studies have demonstrated associations between PGS-EA and general cognitive ability (Plomin & von Stumm, 2018), a smaller body of work has shown associations between PGS-EA and specific neurocognitive skills that underlie general cognitive ability. PGS-EA has been significantly associated with vocabulary, executive function (inhibitory control, working memory), and episodic memory in children and adolescents (Domingue et al, 2015;Judd et al, 2020;Loughnan et al, 2021;Rea-Sandin et al, 2021). In a largely separate literature, greater family income and parental education have been significantly associated with higher levels of these neurocognitive skills (Lawson et al, 2017;Merz et al, 2019;Noble et al, 2005Noble et al, , 2007.…”
Section: Pgs-ea Socioeconomic Factors and Neurocognitive Measuresmentioning
confidence: 99%